2017
DOI: 10.1038/nrd.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

WD40 repeat domain proteins: a novel target class?

Abstract: Antagonism of protein-protein interactions (PPIs) with small molecules is becoming more feasible as a therapeutic approach. However, successful PPI inhibitors tend to target proteins containing deep peptide-binding grooves or pockets as opposed to the much more common large, flat protein interaction surfaces. Here we review one of the most abundant PPI domains in the human proteome, the WD40 repeat domain (WDR), which has a central peptide-binding pocket. Recently, two WDR proteins, WDR5 and EED, have been suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
243
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 248 publications
(248 citation statements)
references
References 125 publications
(144 reference statements)
4
243
0
1
Order By: Relevance
“…In recent years, targeting PPIs as indicators for clinical diagnosis and therapeutic interventions has become a promising but challenging approach in the field . The focus on WDR domain proteins has increased because of its function as a broad mediator of PPIs . We proposed that hubs (strong connections with other proteins) among WDR domain proteins may be more essential than other non‐hubs to the pathology of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, targeting PPIs as indicators for clinical diagnosis and therapeutic interventions has become a promising but challenging approach in the field . The focus on WDR domain proteins has increased because of its function as a broad mediator of PPIs . We proposed that hubs (strong connections with other proteins) among WDR domain proteins may be more essential than other non‐hubs to the pathology of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that hubs (strong connections with other proteins) among WDR domain proteins may be more essential than other non‐hubs to the pathology of CRC. In our study, we first constructed a bioinformatics strategy, which combined a network hub analysis and CRC‐associated gene analysis based on publicly available data, to identify candidates potentially involved in CRC from 361 known WDR domain proteins . Indeed, genome‐wide studies have shown that deletion of a hub protein is more likely to be lethal than deletion of a non‐hub protein, a phenomenon known as the centrality‐lethality rule .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations